Job description as a management document: legal aspect - S. E. Titor (Вестник университета, 2022)
The job description as an act of the managerial and control function of the employer has a recommendation character. But many employers use it to determine the scope of an employee’s duties, qualification requirements, and responsibilities. In practice, there are many questions and disputes about the possibility of changing job descriptions. Judicial practice on the dismissal legitimacy’s recognition because of the job description change develops in different ways. In this regard, it is important to determine in the legal aspect what a “job description” is. The purpose of the study is to determine the meaning of the job description in the content of labor relations, its role in the personnel management system. The analysis of the job description as a legal phenomenon is implemented by the author through the definitions of labor function and freedom of labor. Analytical, comparative legal methods and a systematic approach made it possible to see the job description as an integral part of the labor function.